PENGEMBANGAN VIDEO PEMBELAJARAN MENGGUNAKAN CANVA UNTUK MENDUKUNG KEMAMPUAN PEMAHAMAN KONSEP SISWA SMP - Lusianty Bakara; Rahma Siska Utari; Verayanti Verayanti (IKIP Siliwangi, 2023)
This type of research is descriptive to describe the development of learning videos using Canva in material relations and functions to support junior high school students' conceptual understanding abilities. The method used in this study is a design research type of development study. The research subjects were 28 students. This research was conducted through the preliminary stages and prototyping stages, including: self evaluation, expert review, one-to-one, small group, and field tests. Data were collected using walkthroughs, tests, questionnaires, and interviews. Walkthrough, test, questionnaire, and interview data were analyzed and presented descriptively. The results of the study show that learning videos developed with Canva are said to be valid and practical and have a potential effect to support students' conceptual understanding abilities with an average yield of 74.79% with the lowest achievement on the indicator of using, utilizing and selecting certain procedures or operations as much as 70% and the highest indicator is 81.67% in the item restating a concept.